Why Do Women Get Cervical Cancer in an Organized Screening Program in Canada?. Issue 1 (January 2019) - Jackson, Rebecca; Wang, Li; Jembere, Nathaniel; Murphy, Joan; Kupets, Rachel
Abstract : Objective: The aim of the study was to determine factors associated with the development of cervical malignancy among women participating in an organized cervical screening program. Materials and Methods: A population-based retrospective cohort study was performed examining the screening histories 2 to 10 years before diagnosis of invasive cancer in Ontario women between 2011 and 2014. Results: A total of 2, 002 cases of cervical cancer were identified; 1, 358 (68%) were squamous cell carcinomas and 644 (32%) were adenocarcinomas. The mean age at the time of diagnosis was 50.3 years. More than 60% of the cohort had at least 1 cytology test within 2 to 10 years of their diagnosis. Of the women having a cytology result 24 to 36 months before diagnosis, 69% had a normal cytology whereas only 7% had a high-grade cytology result. Stage of cancer was most advanced in women who did not have cytology in the 2 to 10 years before their diagnosis. On multivariate regression, those with cervical cancer who were less likely to have undergone screening include older age, advanced stage, lower income, not having a family physician, and those diagnosed with adenocarcinoma. Conclusions: Although nonparticipation in screening is the greatest factor associated with cervical cancer diagnosis, failure of cervical cytology to detect cytologic abnormalities in women 2 to 3 and 3 to 5 years before diagnosis is of concern. Efforts must be directed to recruitment of women for screening as well as improving the sensitivity of screening tests to detect existing abnormalities. Abstract : Supplemental digital content is available in the text.